Leveraging tobacco for a low-carbon biorefinery - Yin, Quanyu; Zhu, Zhengkang; Chen, Yujia; Yang, Mengquan (Frontiers in Plant Science, 2025)
Tobacco has historically served as a high-value cash crop within the cigarette industry. However, increasing public health concerns and climate change mitigation objectives are driving a reassessment of its applications. Given its substantial biomass yield and well-established agricultural infrastructure, tobacco is being investigated as a potential renewable energy crop. Recent studies indicate that tobacco leaves can be effectively converted into fermentable substrates through a straightforward autoclave-based hydrolysis process, yielding a nutrient-rich solution suitable for biofuel fermentation and offering a favorable environmental profile. Building on these insights, this perspective evaluates the potential of utilizing tobacco as a feedstock in low-carbon biorefineries. We conduct a critical analysis of recent advancements in biomass conversion, life cycle assessment, utilization of agricultural residues, microbial compatibility, agronomic and genetic enhancements, land-use implications, and policy frameworks. Key challenges and future research directions are identified to facilitate the transformation of tobacco from a contentious crop into a source of sustainable fuels and bioproducts.